Actively Interacting: Christian Preschool Teachers' Efforts to Prevent Phubbing Behavior in Early Age Children Who Are Addicted to Gadgets - Suarman Zai; Suardin Zai; Elieser R Marampa; Marthen Mau (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
This article aims to contribute ideas in preventing phubbing behavior in young children who are addicted to gadgets and to place an active, interactive-based approach in order to help children develop social skills well in their social environment. The method used is descriptive analysis with a systematic literature review approach. The findings of this research show that the internet or digital world which is easily accessed by young children via gadgets opens up space for ignoring the person they are talking to when communicating, which is also known as phubbing which is caused by irregular use of gadgets. Additionally, children who grow up in environments where excessive gadget use is allowed or even encouraged by parents tend to experience problems with social skills, including the ability to give others their full attention without being distracted by gadgets. Therefore, parents must pay full attention to this problem through holistic assistance to prevent bad things from happening in the future.